Schmid metaphyseal chondrodysplasia: consideration in differential diagnosis of rickets - Lalitha, Parvathy; Catherine, Ann Mary (International Journal of Contemporary Pediatrics, 2024)
Schmid metaphyseal chondrodysplasia is a rare inherited cause of skeletal dysplasia caused by COL10A1 gene mutation, characterized by skeletal abnormalities and progressive short stature not usually associated with any other major anomalies or cognitive disability. We report a case of a 3-year-old girl with short stature, genu varum, and motor developmental delay, who was initially misdiagnosed and treated as rickets. Blood investigations and radiographic findings were crucial to guide the diagnosis. Genetic testing allows definitive molecular diagnosis leading to proper treatment and counselling.